2004
DOI: 10.1177/1050651904267068
|View full text |Cite
|
Sign up to set email alerts
|

Technical Communication Instruction in Engineering Schools

Abstract: This survey of 73 top-ranked U.S. and Canadian engineering schools examines initiatives that engineering schools are taking to improve communication instruction for their students. The survey reveals that 50% of the U.S. schools and 80% of the Canadian schools require a course in technical communication. About 33% of the schools utilize some form of integrated communication instruction, and another 33% offer elective courses in communication. Just 10 schools have created engineering communication centers to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…A study published in 2004 [10] revealed some general conclusions about graduates' communication skills that should be taken into consideration:…”
Section: An Example Of Competency Integration: Communication Skillsmentioning
confidence: 99%
“…A study published in 2004 [10] revealed some general conclusions about graduates' communication skills that should be taken into consideration:…”
Section: An Example Of Competency Integration: Communication Skillsmentioning
confidence: 99%
“…The research into the writing instruction provided to engineering students and engineers, including Reave [1] and Winsor [2], shows that there is a clear lack of focus on the ability to convey thoughts and ideas through writing. What has been shown in studies such as Brady [3] is that what is taught in college concerning compositional style, strategies, and techniques is often remembered and applied to later writing situations in the workplace.…”
Section: Inadequate Compositional Instructionmentioning
confidence: 99%
“…In response, universities have rushed to provide new programs and special courses to prepare engineering students for the writing that is required in their field [1]. Several universities have recognized the need for specific english classes for engineering majors; however, few of the courses are actually taught by engineering professors.…”
Section: Introductionmentioning
confidence: 99%